2015
DOI: 10.1589/jpts.27.1227
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of stress and muscle activity of patients with different degrees of temporomandibular disorder

Abstract: [Purpose] Temporomandibular disorder is one of the many different adverse health conditions that can be triggered by stress. Therefore, a biopsychosocial model has been proposed to characterize the multifactorial nature of temporomandibular disorder. The aim of the present study was investigate the correlation of salivary cortisol levels with the activities of the masseter and anterior temporal muscles of patients with different degrees of temporomandibular disorder. [Subjects and Methods] Forty-nine women bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
1
17
1
1
Order By: Relevance
“…De Paiva Tosato al. [9], Lauriti et al [10] and Mazzetto et al [62] showed that EMG activity of the chewing muscles was positively correlated with the severity of TMD. Regarding TMD severity, our study found no correlation between jaw function limitations and raw and normalized EMG values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Paiva Tosato al. [9], Lauriti et al [10] and Mazzetto et al [62] showed that EMG activity of the chewing muscles was positively correlated with the severity of TMD. Regarding TMD severity, our study found no correlation between jaw function limitations and raw and normalized EMG values.…”
Section: Discussionmentioning
confidence: 99%
“…The Research Diagnostic Criteria for Temporomandibular Disorder (RDC/TMD) is considered the most comprehensive tool for diagnosing and classifying TMD in myofascial pain, joint disc alterations, arthralgia, arthritis and osteoarthritis [8,9]. Surface electromyography (sEMG) can contribute to knowledge of muscle physiology as a complementary instrument in TMD assessment, as well as differential diagnosis and TMD monitoring [10].…”
Section: Introductionmentioning
confidence: 99%
“…(1,6) This muscular adaptation, which the temporal muscle assumes the additional function to compensate the loss of the masseter muscle strength, may occur to minimize pain in a motor response in individuals with TMD. (17) Alterations in the electrical activity of masticatory muscles in patients with TMD has been related to muscle pain, emotional factors, stress and tension, moreover, greater muscle asymmetry can be observed in this group of patients during the sitting evaluation and MI. (18,19) As the results of this study, authors demonstrated in their study a greater activity of the left anterior temporal than the masseter in patients with TMD, when evaluated during MI.…”
Section: Discussionmentioning
confidence: 97%
“…The study regarding the influence of stressogenic professions on the degree of sleep bruxism manifestations was performed according to the criteria proposed by Nishimura [21]. We have applied questionnaires for the quantitative assessment of SB manifestations [22][23][24][25]: clinical questionnaire, Fonseca questionnaire, multifactorial questionnaire for bruxism associated pain, sleep quality questionnaire. For the quantitative assessment of the emotional subjective feelings, we have used the Visual Analogue Scale (VAS).…”
Section: Methodsmentioning
confidence: 99%